1994
DOI: 10.1095/biolreprod50.6.1357
|View full text |Cite
|
Sign up to set email alerts
|

Testis-Specific RT7 Protein Localizes to the Sperm Tail and Associates with Itself1

Abstract: The RT7 gene recently cloned by us is expressed as an abundant RNA in round spermatids. In vitro transcription-translation showed that the RT7 gene encodes a protein of 26-27 kDa on SDS-polyacrylamide gels. Here we report the development of monoclonal antibodies (mAbs) raised against a peptide from the predicted N-terminal amphipathic alpha-helix of the rat RT7 protein. All mAbs recognize RT7 protein or N-terminal parts of it. To investigate RT7 in vivo, mAbs were used in immunofluorescence microscopy and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
2
16
0
2
Order By: Relevance
“…Izumo sperm-egg fusion 1 (Izumo1) (11) and AKAP82, the major protein of the fibrous sheath of the sperm flagellum (12), were present in the membrane and FS fractions, respectively. Odf1, the major ODF protein (13), was extracted only with urea (Fig. 5B).…”
Section: Mca Homozygous Mutant Malesmentioning
confidence: 99%
“…Izumo sperm-egg fusion 1 (Izumo1) (11) and AKAP82, the major protein of the fibrous sheath of the sperm flagellum (12), were present in the membrane and FS fractions, respectively. Odf1, the major ODF protein (13), was extracted only with urea (Fig. 5B).…”
Section: Mca Homozygous Mutant Malesmentioning
confidence: 99%
“…Immunoelectron microscopy with the mAb showed that, in mature sperm, KLC3 associates with the surface of ODFs and is present in the space between adjacent ODFs and between mitochondria and ODFs, which are devoid of tubulins (38). KLC3 is not present in the medulla of ODFs, indicating that KLC3 is not an integral ODF protein like ODF1 (36,54) and ODF2 (29,55). Indeed, Western blot analysis of highly purified ODFs failed to detect KLC3 (Fig.…”
Section: Table I Klc3 Binding To Odf1 In Yeastmentioning
confidence: 96%
“…Proteins from fractionated male germ cells obtained by centrifugal elutriation (36,37) or from ODFs and the FS were separated on 10 -15% gradient SDS-polyacrylamide gels and transferred to NitroPlus membranes. Membranes were blocked and washed as described above and were then incubated in Western blot binding buffer (30) containing 1 mM ATP and 1000 cpm/ml 35 S-labeled KLC3 protein, produced by in vitro translation, for 16 h at 4°C.…”
Section: Klc3-odf Binding Assaysmentioning
confidence: 99%
“…The antibodies were affinity-purified by binding them to filterimmobilized MBP-18-8-1 fusion protein as described [14]. Affinity-purified anti-OIP1 antibodies were used 1) in Western blotting experiments to detect testicular OIP1 protein as described [12] using protein extracts isolated from testis, spermatozoa, heart, and smooth muscle; and 2) in indirect immunofluorescence analysis of formaldehyde-fixed, Triton-permeabilized rat epididymal spermatozoa using Cy-3 conjugated goat anti-rabbit sera as described [11,16].…”
Section: Oip1 Protein Analysismentioning
confidence: 99%
“…The second ODF1 structural feature is a C-terminal CysGly-Pro (CGP) repeat [16], also present in the Drosophila Mst(3) CGP gene family [17][18][19]. The Mst(3) gene family is composed of seven genes, five small genes of similar size and exon-intron structure (Mst87F, Mst84Da, Mst84Db, Mst84Dc, and Mst84Dd) and two tandemly ar-544 ZARSKY ET AL.…”
Section: Introductionmentioning
confidence: 99%